Management Competence and Incompetence Training: Theory and Practice - De Villiers, Rouxelle (Auckland University of Technology, 2013)
Several highly regarded scholars in management claim that educational methodologies using different management paradigms serve to increase incompetency in thinking and deciding by executives. Evidence-based testing of these claims is rare; however, and examinations of such claims have telling weaknesses (e.g., lacking in comparable control and treatment groups).This study examines andragogical methods (i.e., learning strategies focused on adults) and their effectiveness (or lack thereof) in improving sense-making and decision-making competencies in graduate managers in master of business administration (MBA) programmes. The thesis tests several hypotheses using an experimental design, involving 150 MBA students and executive learners. The study includes a series of four in-basket simulations and role-plays simulating decision-making scenarios versus traditional lecture trainer-learner formats. Three decision categories (Human Resources, Marketing, and General Management) are tested in the four in-basket simulations and simulated interactions as well as independent thought. The study examines, through the application of fuzzy set qualitative comparative analysis (fsQCA) procedures, the effect of goal-based scenarios; devil’s advocate dissent; group versus individual decision-making using different processing tools; accessing implicit knowledge; and “drop your tools” training on decision competency and incompetency outcomes as well as decision confidence. Laboratory experiments, involving 150 MBA graduates and Alumni from four universities across New Zealand, test 13 propositions. The findings provide evidence supporting the viability of testing training theory and tools that increase competency as well as incompetency in business-related decisions.
Keywords: Teaching methodologies; Marketing; MBA; Andragogy; fsQCA; In-baskets; Decision-making; Sense making; Group interactive decisions; Goal based scenarios; Case based learning; Heuristics; Management development; Confidence; Competence